Acral Melanoma in the Caucasian Population: A Comprehensive Cohort Study on Epidemiological, Clinicopathological, and Prognostic Features - J. Angel-Baldo; S. Podlipnik; A. Azón; A. Boada; A. Arrieta; J. Marcoval; C. López-Sánchez; M. Sàbat; S. Segura; D. Bodet; N. Curcó; D. Lopez-Castillo; et al. (Actas Dermo-Sifiliográficas)
Background: Acral melanoma is associated with poor prognosis. Studying the characteristics and prognosis of Caucasian patients is crucial to understand the distinct features of this tumor. Objectives: To analyze the epidemiological, clinicopathological, and prognostic features of acral melanoma in Caucasian patients. Methods: We conducted a retrospective, multicenter, cohort study of acral melanoma from a database across 20 hospitals from South Europe from January 2000 to December 2019. Results: A total of 733 acral melanomas were identified (median age, 67.5 years; 95.2%, Caucasians; 77.5% of which were located on the feet). Overall, 77.5% of cases were invasive melanomas. Foot melanomas had a higher proportion of invasive cases (80.8% vs 69.8%; p = 0.003), stages III and IV at diagnosis (24.8% vs 11.7%; p < 0.001), thicker Breslow depth (2.8 mm vs 2.0 mm; p = 0.021) and a higher rate of positive sentinel lymph node biopsy (SLNB) (30.7% vs 15.7%; p = 0.012). Thicker Breslow depth and later age of onset were risk factors for melanoma-specific survival. Thicker Breslow depth and ulceration were independent prognostic factors of relapse-free survival. Melanoma location and histopathological subtype were not associated with worse prognosis. Recurrences were a common finding (27.7%), with distant metastases appearing earlier than locoregional recurrences (1.32 years [IQR, 1.12–1.87] vs 2.14 years [IQR, 1.68–2.70]; p = 0.015). Conclusion: This study, the largest in a predominantly Caucasian population, underscores the unfavorable outcomes of acral melanoma. Foot melanomas exhibited delayed detection, increased invasiveness, thicker Breslow depth, increased SLNB involvement, and higher AJCC stages. The high recurrence rate and early distant metastases emphasize the critical role of intensive follow-up and routine imaging modalities to detect asymptomatic relapses. Resumen: Introducción: El melanoma acral está asociado con un pronóstico desfavorable. El estudio sobre las características y el pronóstico en los pacientes caucásicos puede ser crucial para comprender las características distintivas de este tumor. Objetivos: Analizar las características epidemiológicas, clinicopatológicas y pronósticas del melanoma acral en los pacientes caucásicos. Material y métodos: Estudio de cohorte retrospectivo de melanoma acral a partir de una base de datos multi-institucional en 20 hospitales españoles, entre enero de 2000 y diciembre de 2019. Resultados: Se identificaron un total de 733 melanomas acrales (edad media: 67,5 años, el 95,2% caucásicos y el 77,5% en los pies). En general, el 77,5% de los casos fueron invasivos. Los melanomas localizados en los pies tuvieron una mayor proporción de casos invasivos (80,8 vs. 69,8%; p = 0,003), estadios III y IV al diagnóstico (24,8 vs. 11,7%; p < 0,001), valores de Breslow más altos (2,8 vs. 2,0 mm; p = 0,021) y una mayor tasa de positividad de biopsia selectiva del ganglio centinela (BSGC) (30,7 vs. 15,7%; p = 0,012). Un mayor grosor de Breslow y una edad de aparición más tardía fueron factores de riesgo para menor supervivencia específica por melanoma. Un mayor grosor de Breslow y la ulceración fueron los factores pronósticos independientes menor supervivencia libre de recaída. La localización del melanoma y el subtipo histopatológico no se asociaron con un peor pronóstico. Las recurrencias fueron frecuentes (27,7%), con a distancia apareciendo antes que las recurrencias locorregionales (1,32 años [IQR: 1,12-1,87] vs. 2,14 años [IQR: 1,68-2,70]; p = 0,015). Conclusión: Este estudio, el mayor en una población predominantemente caucásica, subraya los resultados desfavorables del melanoma acral. Los melanomas en los pies mostraron una detección tardía, mayor proporción de melanomas invasivos, valores de Breslow más profundos, mayor positividad o afectación de BSGC y estadios AJCC más altos. La alta tasa de recurrencia y las metástasis a distancia tempranas enfatizan el papel crítico del seguimiento intensivo y las pruebas de imagen rutinarias para detectar recaídas asintomáticas.